An Automated Skull-Stripping Method by Windowing the Histogram - Sarkar, S; Mandal, A; Sarkar, K (International Journal of Computer Sciences and Engineering, 2025)
An automated method for segmentation of Magnetic Resonance (MR) head images into brain and non-brain has been proposed. It combines the strategy used in intensity and morphological skull-stripping methods. The method is very fast and requires no preprocessing of MR images. It is testified on T1-Weighted MR image modality and produces accurate output.